PERLINDUNGAN HUKUM FRANCHISOR DAN FRANCHISEE DALAM PERJANJIAN WARALABA âSOTO SEGEER MBOK GIYEMâ BOYOLALI - , RizkiNurAnnisa, Adi Sulistiyono (PRIVAT LAW II, 2016)
AbstractThis study aimed to determine the form of legal protection for trademark holders to the culinary business in Indonesia and the reasons a franchiseein the franchise agreementon